Modeling and Analysis of Resistance-Sensing Characteristics for Two-Way Shape Memory Alloy-Based Deep-Sea Actuators - Jian Guo; Binbin Pan; Weicheng Cui; Huiming Xiang (Journal of Marine Science and Engineering)
Deep-sea actuators based on shape memory alloys (SMAs) are an emerging frontier field of multidisciplinary crossover, and the resistive sensing characteristics are the basis for the drive control of SMA deep-sea actuators. The resistance and resistivity of SMAs are complex and highly dependent on temperature and stress, and there is no complete description of SMAs for extreme environments of high pressure, low temperature, and high salinity in the deep sea. In this study, the logistic function is introduced to improve the kinetic equation of phase transition, and the macromechanical model, the law of resistance, and the resistivity mixing rule are integrated to model and analyze the resistive self-awareness characteristics of two-way shape memory alloy deep-sea actuators. The complex coupling relationships among resistance, strain, stress, resistivity, and temperature under constant load conditions are investigated, and the validity of the resistance-sensing model is verified by the water bath cycling test. The results show that the predicted values of the model agree well with the measured values. The self-perceived relationship between the resistance and deformation of the two-way shape memory alloy can be effectively expressed, which provides theoretical model support for the design of memory alloy deep sea actuators and sensorless drive control.